Silencing of SAA1 inhibits palmitate- or high-fat diet induced insulin resistance through suppression of the NF-κB pathway - Wang, Yong (Mol Med, 2019)
BACKGROUND: Obesity is one of the leading causes of insulin resistance. Accumulating reports have highlighted that serum amyloid A-1 (SAA1) is a potential candidate that is capable of attenuating insulin resistance. Hence, we conducted the current study with aims of investigating our proposed hypothesis that silencing SAA1 could inhibit the progression of obesity-induced insulin resistance through the NF-κB pathway. METHODS: Gene expression microarray analysis was initially performed to screen differentially expressed genes (DEGs) associated with obesity. Palmitate (PA)-induced insulin resistance Huh7 cell models and high-fat diet (HFD)-induced mouse models were established to elucidate the effect of SAA1/Saa1 on insulin resistance. The NF-κB pathway-related expression was subsequently determined through the application of reverse transcription quantitative polymerase chain reaction (RT-qPCR) and Western blot analysis. RESULTS: Saa1 was identified as an obesity-related gene based on the microarray data of GSE39549. Saa1 was determined to be highly expressed in HFD-induced insulin resistance mouse models. PA-induced Huh7 cells, treated with silenced SAA1 or NF-κB pathway inhibition using BAY 11–7082, displayed a marked decrease in both Saa1 and SOCS3 as well as an elevation in 2DG, IRS1 and the extent of IRS1 phosphorylation. HFD mice treated with silenced Saa1 or inhibited NF-κB pathway exhibited improved fasting blood glucose (FBG) levels as well as fasting plasma insulin (FPI) levels, glucose tolerance and systemic insulin sensitivity. Saa1/SAA1 was determined to show a stimulatory effect on the transport of the NF-κBp65 protein from the cytoplasm to the nucleus both in vivo and in vitro, suggesting that Saa1/SAA1 could activate the NF-κB pathway. CONCLUSION: Taken together, our key findings highlight a novel mechanism by which silencing of SAA1 hinders PA or HFD-induced insulin resistance through inhibition of the NF-κB pathway. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s10020-019-0075-4) contains supplementary material, which is available to authorized users.